Pengaruh Tingkat Pengangguran dan Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi di Kabupaten Sidoarjo - Alvira Tania Lidyanti; Nurul Hanifa (Universitas Negeri Surabaya, 2022)
Regional economic development efforts are an important part to achieve the success of national development which can be measured by increasing economic growth. So that there is a need for research to find out the obstacles that hinder economic growth. This study aims to determine the effect of unemployment and poverty rates on economic growth in Sidoarjo Regency. The method used is descriptive quantitative method. The type of data processed is secondary data in the form of time series with a time span of 2010-2020. The analytical method used is multiple linear regression analysis with the help of the IBM SPSS 26 program. The results of this study indicate that partially, the unemployment rate has a significant negative effect and the poverty rate has a significant positive effect. Meanwhile, simultaneously, the unemployment rate and poverty rate affect economic growth in Sidoarjo Regency.